The role of the wave packet coherence on the ionization cross section of He by p+ and C6+ projectiles - Navarrete, Francisco Oscar; Ciappina, Marcelo Fabián; Sarkadi, L.; Barrachina Tejada, Raul Oscar (Elsevier, 2017)
Fil: Navarrete, Francisco Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina